Pengaruh Kualitas Layanan Elektronik, Ekspektasi Performa dan Persepsi Risiko Terhadap Keputusan Penggunaan Berkelanjutan Aplikasi DANA dalam Perspektif Bisnis Islam: Studi pada Pengguna Aplikasi DANA di Bandar Lampung - Baskara Ade Putra; Muhammad Iqbal; Yeni Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the influence of electronic service quality, performance expectancy, and risk perception on the continued usage intention of the DANA application in Bandar Lampung, as well as to explore these findings from an Islamic business perspective. This research employs a quantitative approach with data collected through questionnaires distributed to 100 active users of the DANA application. The data were analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS software. The results show that, partially, electronic service quality and performance expectancy have a positive and significant effect on the continued usage intention of the DANA application. Meanwhile, risk perception has a negative but not significant effect. Simultaneously, all three variables have a significant effect on continued usage intention. From an Islamic business perspective, the DANA application is considered to have made efforts to uphold muamalah principles such as justice, honesty, trustworthiness, and protection of public interest. This is reflected in the transparency of services, user data security, and accessibility for various user groups, particularly micro, small, and medium enterprises. Therefore, the DANA application can be deemed in line with Sharia values as long as it is managed responsibly and ethically.